Odpowiedź :
Odpowiedź:
a)1/2x-x=4-6
-1/2x=-2/×-2
x=4
b)x-1/3x=5+1
2/3x=6/×3/2
x=9
c) x/4=2+1/4
x/4=9/4/×4
x=9
d) x/5-x=3+1/5
-4/5x=16/5/×-5/4
x=-4
e)5/6x-5/6=4
5/6x=4+5/6
5/6x=29/6/×6/5
x=29/5=5 4/5
f)1/2x+3=-x
1/2x+x=-3
3/2x=-3/×2/3
x=-2
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
1/2x-4=x-6
1/2x - x = -6 + 4
-1/2x = -2 /*(-2)
x = 4
b)
x-5=1/3x+1
x - 1/3x = 1 + 5
2/3x = 6 /*3/2
x = 6 * 3/2 = 9
c)
x/4-1/4=2
1/4x = 2 + 1/4 /*4
x = 4 * 2 1/4 = 4 * 9/4 = 9
d)
x/5 - 3 = x + 1/5
1/5x - x = 1/5 + 3
-4/5x = 3 1/5 /*(-5/4)
x = -5/4 * 16/5 = -4
e)
5/6(x - 1) = 4
5/6x - 5/6 = 4
5/6x = 4 + 5/6 /*6/5
x = 6/5 * 4 5/6 = 6/5 * 29/6 = 29/5 = 5 4/5
f)
-1/2(-x-6)=-x
1/2x + 3 = -x
1/2x + x = -3
1 1/2x = -3
3/2x = -3 /*2/3
x = -2
Szczegółowe wyjaśnienie: